Public interest reports as a medium for corporate disclosure: The case of General Motors - Malone, David (Journal of business ethics, 1996)
We examined the public interest reports of General Motors from 1971 to 1990 and presented the contents thereof herein. The principal areas disclosed by GM during those years that are discussed in this paper were minorities, women, and employment issues, energy and the environment, international operations, automotive safety, and philanthropic activity. The purpose of this study was to examine the public interest report as a vehicle through which a firm might disclose information in the public interest. We concluded that there were at least three principal forces driving GM's disclosures. They included public attention focused on, potential costs associated with, and the relative subjectivity of an issue., In reading their public interest reports, it became clear that GM is socially responsive in matters of public interest. Whether they are socially responsible is a judgment not within the scope of this study. However, we do not preclude the possibility that the report may serve as a vehicle which would build a certain momentum in public responsibility, and thus partially drive decisions made by management in social issues.